Change of areas of hair cuticle in sleep cats for nephropathy and polyorganic pathology - Тимошенко, О. П.; Снопенко, О. С. (Scientific Progress & Innovations, 2018)
89 males and females of domestic cats, aged 2.5–10.0 years, were examined. It was established that under different variants of nephropathy and for the development of hepatic and renal hepatic syndromes in domestic cats in the liver and kidneys there are significant structural changes that is reflected in the disturbances of metabolic processes determined by the results of clinical and microscopic and biochemical studies of blood serum, as well as changes in the area of hair cuticle (AHC) of the wool cover of cats. The study of the cuticle was carried out using negative impressions on a nitrocellulose lacquer, which was applied to the slide glass. Hair was removed from him after lacquering. The resulting imprint was analyzed under Carl Zeiss Jena microscope (Ч 400) and set the AHC in the root zone and in the thickest part of the rod, expressing the result in nm2. In 40 % of clinically healthy cats, the size of the hair cuticle (AHC) is 8–9x104 nm2; in 60 % of animals – 10–17x104 nm2. Such a significant spread of indicators is due to different age of animals and the influence of the rock factor. It turned out that 100 % of clinically healthy cats do not have the values of AHC 6–7´104 nm2. The higher the AHC (13х104 nm2 or higher), the less likely an animal is the shelter or the initial form of kidney disease, and there is not one-hundred percent polyorganic hepatic-renal or renal-hepatic pathology. For acute renal failure, AHC values are predominantly in the range of values 13–14´104 nm2, that is, they do not differ from the norm. For chronic renal insufficiency, the value of AHC is 6–10´104 nm2. In general, for kidney diseases, there are no AHC higher than 15 nm2. In polyorganic pathology in the form of hepatic-renal and renal-hepatic AHC syndromes in domestic cats, they are 6–12x104 nm2 and are not completely found outside the given range. In combination with the results of clinical and biochemical studies of blood serum, this technique allows differentiating syndromes depending on the primary link of the pathogenetic chain. It can be used for the dispensary examination of domestic cats, as well as for the study of the animals’ health of other species in normal and in pathology.